162k views
2 votes
Solve the system of equations. 2x + 3y = 6 x + y = 4 (6, -2) (-2, 6) (-3, 4) (0, 2)

User Kye
by
4.6k points

2 Answers

3 votes

Answer:

(6,-2)

Explanation:

Given equations are
2x + 3y = 6 and
x + y = 4.

Solve 2nd equation
x + y = 4 for y


x + y = 4


y = 4-x ...(i)

Plug value of y from equation (i) into first equation
2x + 3y = 6


2x + 3(4-x) = 6


2x + 12-3x = 6


12-x = 6


-x = 6-12


-x = -6


x = 6

Plug x=6 into equation (i)


y = 4-x


y = 4-6


y = -2

Hence final answer is x=6, y=-2 or we can write that in (x,y) form as (6,-2)

User Marco Rinck
by
4.4k points
2 votes

Answer:

(6,-2)

Explanation:

2x + 3y = 6

x + y = 4

Multiply the second equation by -2 to eliminate x

-2(x+y) = -2*4

-2x-2y = -8

Add this to the first equation

2x + 3y = 6

-2x -2y = -8

---------------------

y = -2

Now we need to find x

x+y = 4

x-2 = 4

Add 2 to each side

x-2+2 = 4+2

x = 6

(6,-2)

User Shridhar Gupta
by
4.7k points